Gut Microbial Flora, Prebiotics, and Probiotics in IBD: Their Current Usage and Utility. (7th August 2013) - Scaldaferri, Franco; Gerardi, Viviana; Lopetuso, Loris Riccardo; Del Zompo, Fabio; Mangiola, Francesca; Boškoski, Ivo; Bruno, Giovanni; Petito, Valentina; Laterza, Lucrezia; Cammarota, Giovanni; Gaetani, Eleonora; Sgambato, Alessandro; et al.
Abstract : Inflammatory bowel diseases are chronic diseases affecting the gastrointestinal tract, whose major forms are represented by Crohn's disease (CD) and ulcerative colitis (UC). Their etiology is still unclear, although several factors have been identified as major determinants for induction or relapses. Among these, the role of the "forgotten organ", gut microbiota, has become more appreciated in recent years. The delicate symbiotic relationship between the gut microbiota and the host appears to be lost in IBD. In this perspective, several studies have been conducted to assess the role of prebiotics and probiotics in gut microbiota modulation. This is a minireview aimed to address in an easy format (simple questions-simple answers) some common issues about the theme. An update on the role of selected constituents of gut microbiota in the pathogenesis of IBD is presented together with the analysis of the efficacy of gut microbiota modulation by prebiotics and probiotics administration in the management of IBD.